Introduction: Searching for the Natural Origins of Content: Challenging Research Project or Benighted Quest? - Hutto, Daniel D. (2015)
This paper introduces this special issue which is focused on its target paper - The Natural Origins of Content. The target paper has had a robust and considered set of fifteen replies; a literal A to Z of papers (from Abramova’s to Zawidzki’s). This extended introduction explains the background thinking and challenges that motivated the target article's proposed research programme. It also provides a sneak peak preview and navigational aid to the special issue’s contents. Brief highlights of each commentary are provided and they are grouped together under broad headings. We do not attempt to give detailed replies to these suggestions or answer the various critiques at this stage of the proceedings: that is for future work.